2007
DOI: 10.1002/asi.20751
|View full text |Cite
|
Sign up to set email alerts
|

Blogging activity among cancer patients and their companions: Uses, gratifications, and predictors of outcomes

Abstract: This study examines cancer patients' and companions' uses and gratifications of blogs and the relationship between different types of blogging activities and gratification outcomes. In an online survey of 113 respondents, cancer patients were found to be more likely than their companions to host their own blogs. Four areas emerged as gratifications of blog use: prevention and care, problem-solving, emotion management, and information-sharing. Cancer patients and companions both found blogging activity to be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 46 publications
6
93
0
3
Order By: Relevance
“…Furthermore, since there is a dearth of comparable studies on blogs as forums of information seeking and sharing in everyday contexts, the evaluation of the findings is rendered difficult. However, the results have similarities with the findings of Chung and Kim's (2008) study. It showed that for cancer patients and companions blogs function primarily as tools for emotion management and information sharing rather than as tools for information seeking that serve the ends of problem solving.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, since there is a dearth of comparable studies on blogs as forums of information seeking and sharing in everyday contexts, the evaluation of the findings is rendered difficult. However, the results have similarities with the findings of Chung and Kim's (2008) study. It showed that for cancer patients and companions blogs function primarily as tools for emotion management and information sharing rather than as tools for information seeking that serve the ends of problem solving.…”
Section: Discussionsupporting
confidence: 85%
“…[28] Bir çalışmada blogların kanser hastaları ve yakınları için duygu yönetimi ve bilgi paylaşımı açısından yararlı bir araç olduğu gösterilmiştir. [29] İnternet bilgi paylaşımı açısından önemli bir alan oluşturmaktadır, ancak internetten edinilen bilgiler her zaman doğru olmayabilir. Ayrıca sağlık personeli hastaya bilgi verirken hastalığın sürecini ve hastanın gereksinimlerini …”
Section: Kanser Hastalarının Bilgi Kaynaklarıunclassified
“…And finally, Chung and Kim [35] reported that blogs are perceived as credible sources of information on prevention and care in their self-administered questionnaire survey of 113 members of a cancer-related blog frequented by patients and carers.…”
Section: Published As: Hardiker Nr Grant Mj Factors That Influence mentioning
confidence: 99%